ANALISIS KESALAHAN KAIDAH PENULISAN LAPORAN PENELITIAN - Mara Untung Ritonga; Tribel Tampubolon; Tania Br Tampubolon; Sri Muliani Waruwu; Senna Destini Hutapea; Amanda Putri; Cicilia Nofitaria Br Zebua (STKIP Subang, 2026)
This study aims to identify and analyze various types of writing rule errors in research reports based on a literature review of previous studies. The research method used is a library research with a descriptive qualitative approach. The data were obtained from journal articles, books, and scientific studies relevant to the topic of students’ academic writing errors. Data collection was conducted through documentation study, while data analysis employed the interactive model proposed by Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings show that writing rule errors in academic papers commonly occur in several aspects, namely Indonesian spelling, diction, sentence structure, paragraph development, as well as citation and reference list formatting. The most dominant errors are spelling mistakes, particularly in the use of capital letters, punctuation marks, and prepositions. These findings indicate that students’ academic writing skills still need to be improved, both in linguistic aspects and academic writing conventions